O turismo étnico afro na mina Du Veloso: um estudo do equipamento interpretativo do patrimônio de Ouro Preto/MG - Luiz Cláudio Alves Viana (2021)
When tourism is linked to the cultural heritage of a given society, history and memory became intertwined to create a relationship between subjects and the territory. Then, a humanist character existing in tourism, as a social phenomenon, and in heritage, as a representation cultural becomes. Therefore, understanding the interfaces of cultural tourism and Brazilian cultural heritage, based on official historiography, is necessary to know its limitations and the problems of exclusion of heritage assets of AfroBrazilian culture in national heritage protection policies. In this study, we required to understand how AfroBrazilian tourism can serve as an instrument for the recognition, appreciation and propagation of culture, history and memory placed on the heritage assets of African origin in Brazil. With this, it brought the understanding of AfroBrazilian tourism established by researchers such as Grunewald (2003), Trigo & Netto (2011), Souza & Pinheiro (2018) and others, who understand AfroBrazilian tourism as an instrument to bring other perspectives on AfroBrazilian culture, reinterpreting places and black people as historical agents through tourism. The general objective of this work is to analyze the Mina Du Veloso, located in Ouro Preto/MG, and the work of historical redefinition of that place and the enslaved miners, recognizing the remaining structures of gold mining at 18th century as heritage and symbol that represents the African intelligence in the city. The research methodology was based on a documentary survey of primary sources and related studies. Prosopography was used as a method to understand the ethnic behaviour of people who work at Mina Du Veloso. The participant observation in loco and the interviews were the techniques used to collect data from the observed group. Finally, the tourist proposal of using Afrocentered history to reframe the history of African mining peoples, the territory and the heritage present in it, also contributed to reframe the life history of local people, especially those who work in the touristic space.